Institutional Aspects of Integration in the EEU: Problems and Prospects - JEMELJANOVA, Natalja; KARTASHKIN, Vladimir; MESHCHERYAKOVA, Olga; SMBATYAN, Anait (Journal of Advanced Research in Law and Economics; Vol 8 No 3 (2017): JARLE Volume VIII Issue 3(25) Summer 2017, 2017)
The research aim: the formation, evolution and regularities of the development of the EEU institutional system. The methods used: historicism, systematization, analysis and comparative-legal. The author's position based on the paper relies on the legislation and opinions of the competent scientific environment on the regularities of the development of the institutional system in the integration community and its fundamental influence on the developmental features of the entire integration process. Based on the legal analysis of the EEU norms, differentiation of the characteristic features of the institutional system is carried out. The issues of legal regulation of the ways of decision-making by the institutions of the integration community are raised through the provisions of the constitutive acts of the EEU. As a result of the research, the importance of the correct choice of the organizational and legal forms of the institutional system was revealed not only for its effective functioning, but also for the further progressive development of the entire integration process as a whole.